Efektifitas Penerapan Intervensi Akupressur pada Titik P6, Li4 dan St36 Untuk Menurunkan Mual Muntah pada Pasein Ca Mammae : Studi Kasus - Safrudin, Bachtiar; Rahmawati, Erika (Lontara Journal of Health Science and Technology, 2025)
Acupressure is one of the complementary therapies that can be done on chemotherapy patients to reduce nausea and vomiting. The purpose of this study was to describe the effect of acupressure on Points P6, Li 4 and St 36 in reducing acute nausea and vomiting in Ca Mammae patients undergoing chemotherapy. This research method used a special study approach and literature review with 2 respondents and 4 articles that were reviewed by linking the managed cases. Data analysis techniques in data collection used article analysis and nursing care through stages to evaluation. The research instrument used the Index of Nausea, Vomiting, and Retching (INVR) tools and nursing care formats. The results of this study where 4 articles explained the effectiveness of acupressure at points P6, Li 4 and St 36 were effective in suppressing nausea and vomiting. While the effectiveness of the intervention was seen from the results of the acupressure evaluation where within 3 days of management showed a change in the scale of nausea from moderate to mild.